Gestión interna de residuos de construcción en la ejecución de obras civiles. - Morocho Morocho., Marcia Janeth (2017)
The problem of the Management of Construction and Demolition Waste produced by Civil Works has accompanied man throughout history, being the abandonment of the material the easiest and most common method to date. We have evolved over time and without being knowledgeable of history, it is clear that in the past the impact of their actions on the environment was depreciable. Now in the 21st century because of its development and population growth, the generation of solid waste requires better attention because of its high degree of pollution to the environment. With the bibliographical revision made to articles of scientific journals data has been collected that allows us to know the correct practice of model for the Internal Management of Construction Waste and demolition. This model suggests that in any project before starting construction activities an internal management plan should be implemented for the operation of construction waste and to mitigate the quantities that will be generated through an early and timely identification of This type of materials as they appear in the construction of the same. In order to obtain effective results it is necessary that all people participate in waste management, from the workers to the director of work you know and encourage the actions of reducing reuse and recycling directing all their actions towards the main objective that is the management Environmental protection of waste. It will not always be possible to apply the three actions at the same time or from the technical point of view and from the environmental point of view each case will be particularly evaluated and the ones that fit the most as they are applied will be applied.